High prevalence of sexually transmitted diseases in a rural area in Mozambique. Issue 6 (December 1993) - Vuylsteke, B; Bastos, R; Barreto, J; Crucitti, T; Folgosa, E; Mondlane, J; Dusauchoit, T; Piot, P; Laga, M
Abstract : OBJECTIVE–To assess the extent of the sexually transmitted diseases (STDs) problem in a rural area of Mozambique. METHODS–A cross sectional study among pregnant women and patients presenting with genital complaints. Laboratory confirmation was done for gonorrhoea, chlamydial infection, active syphilis, trichomoniasis and HIV infection. SETTING–A primary health care setting in Vilanculos, Inhambane province, Mozambique. RESULTS–Evidence of one or more of the above STDs was found in 51% of 201 pregnant women, 56% of 85 women and 62% of 77 men with genital complaints. Neisseria gonorrhoea or Chlamydia trachomatis were found in 16% of pregnant women, 23% of female patients and 28% of male patients; genital ulcer disease was present in 6%, 28% and 36%, of respectively pregnant women, female and male patients. The prevalence of active syphilis was about the same in the three groups of study subjects, that is 15%. HIV infection was found in 4% of the male patients; no HIV infection could be detected in the female groups. CONCLUSION–STDs were a major health problem in this rural area in Mozambique. Though HIV infection was still low, the high prevalence of STDs indicates that the potential is there for an explosive spread of the HIV/AIDS epidemic.